Migration, poverty, and inequality: Evidence from Burkina Faso - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2008)
This paper applies Gini and concentration coefficient decomposition as well as the Foster-Greer-Thorbecke poverty index and a welfare function to new data from Burkina Faso to test the relationship between long-distance international migration and internal migration within the African continent and inequality, poverty, and social welfare in rural households. Findings support our theoretical expectation that this relationship varies by migrant destination. We find evidence of a negative correlation between internal migration and inequality and a positive correlation between international migration and inequality. International migration, which involves high costs and risks, appears to be mainly accessible to already wealthy households. Comparatively high remittances from this form of migration are associated with greater inequality. We also find that although international migration is associated with a much lower incidence, depth, and severity of poverty, its impact on social welfare is limited because the beneficiaries of international migration do not include the rural poor.